Medium-fidelity simulation in clinical readiness: a phenomenological study of student midwives concerning teamwork - Zukiswa Brenda Ntlokonkulu; Ntombana Mc'deline Rala; Daniel Ter Goon (BMC, 2018)
Abstract Background Teamwork during obstetric emergency ensures good outcomes for both the woman and her baby. Effective teams are characterised by mutual respect, support, and cooperation among team members. Methods This qualitative, interpretive, phenomenological analysis study was conducted on a purposive sample of five, fourth-year Bachelor of Nursing Science student midwives at the University of Fort Hare (UFH). In-depth semi-structured interviews were conducted. Data analysis applied the interpretative phenomenological analysis method. Results Superordinate theme demonstrated teamwork elicited four clustered themes namely delegation of duties, the importance of teamwork, team support, and confident team leader. The participants recognised that there should be a team leader who is capable of delegating duties to other team members in the management of an obstetric emergency, Participants were confident not only to assign duties but to be kept updated of the intervention. They expressed the need to work collaboratively as a team to achieve the desired goal of providing quality care to the woman. The participants maintained that the team must be supportive and be able to help in decision making during simulation of an obstetric emergency. A sense of mutual respect is echoed by some participants in the process of caring for the woman. Some participants were confident at being team leaders and could see themselves as leaders in the real-life clinical situation. Conclusion The participants acknowledge the importance of teamwork in resolving obstetric emergencies. The importance of delegating duties to other team members, providing updated progress report ensures better outcomes for the woman.